Analisis Hermeneutika Roma 12:2 : Transformasi Pikiran dalam Kehidupan Kristen - Marlince Diana Lende; Junidar Gulo; Malik Bambangan (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2024)
The purpose of this study is to understand Romans 12:-2 from a hermeneutic point of view, especially in relation to the concept of "renewal of the mind" as the key to spiritual transformation in the Christian life. Paul emphasizes the importance of a profound inner change in order to be in harmony with God's will, which is not only a change in behavior, but also a change in mindset influenced by God's Word. Paul's letter to the church in Rome, written to the church in Rome, teaches about salvation through faith and the relationship between the Law and faith in Christ. In Romans 12:2, Paul exhorts believers not to follow worldly values, but to have experiences that renew their minds so that they understand God's will. This hermeneutic interpretation suggests that the renewal of the mind leads believers to live differently from the norms of the world, which affects all aspects of daily life, including relationships with others. However, challenges arise from cultural influences, world customs, and personal weaknesses that hinder change. The results of this study show that the transformation of the heart and mind that Paul teaches is an ongoing spiritual journey that requires dedication, discipline, and patience. This change enables believers to live according to God's good, pleasing and perfect will and bear witness to the world in the truth.